Tingkat Organizational Identification Diantara Mahasiswa - Nilasari, B Medina (Manajemen Bisnis Kompetensi, 2019)
This study investigates the organizational identification level of college student. How is the effect of ras, college degree, campus, length of education, and residence on organizational identification. The proposed hypotheses were tested with a sample of 259 students in Trisakti – Jakarta Barat. Testing of research problems shows that only ras influences the level of organizational identification of Trisakti students. Departing from the conclusions above, the results of this study should be used by the college in managing its students. College must investigate action plans that will be implemented to make effective interventions that will increase the level of organizational identification among students.Keywords: Organizational identification, ras, college degree, length of education